2014
DOI: 10.1021/bi5007942
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule +TIP Protein EB1 Binds to GTP and Undergoes Dissociation from Dimer to Monomer on Binding GTP

Abstract: The +TIP protein EB1 autonomously tracks the growing plus end of microtubules and regulates plus-end dynamics. Previous studies have indicated that EB1 can recognize GTP-bound tubulin structures at the plus end, and it localizes on the microtubule surface at a site close to the exchangeable GTP-binding site of tubulin. Although the GTP-dependent structural change in tubulin has been demonstrated to be a critical determinant for recognition of plus ends by EB1, the effect of GTP on the structure of EB1 has rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The plasmids containing spc34 and dad1 with 6xHis-tag were expressed under induction of arabinose 8 . All the His-tagged and GST-tagged proteins were expressed in Escherichia coli BL21-DE3 cells and purified by Ni 2+ -NTA (QIAGEN) and glutathione Sepharose (GE Healthcare), respectively 56 . Tubulin was purified from goat brain by repetitive cycles of polymerization and depolymerization 56 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmids containing spc34 and dad1 with 6xHis-tag were expressed under induction of arabinose 8 . All the His-tagged and GST-tagged proteins were expressed in Escherichia coli BL21-DE3 cells and purified by Ni 2+ -NTA (QIAGEN) and glutathione Sepharose (GE Healthcare), respectively 56 . Tubulin was purified from goat brain by repetitive cycles of polymerization and depolymerization 56 .…”
Section: Methodsmentioning
confidence: 99%
“…All the His-tagged and GST-tagged proteins were expressed in Escherichia coli BL21-DE3 cells and purified by Ni 2+ -NTA (QIAGEN) and glutathione Sepharose (GE Healthcare), respectively 56 . Tubulin was purified from goat brain by repetitive cycles of polymerization and depolymerization 56 . Protein concentrations were estimated using the Bradford method using BSA as standard 57 .…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of the EB1 COOH-terminal domain reveals a novel homodimeric-fold comprised of a coiled coil and a four-helix bundle motif (12). A recent study reported a GTP-dependent mechanism of dimer-to-monomer transition in EB1 (15). Moreover, ϩTIPs functioning is controlled by conformational modifications.…”
mentioning
confidence: 99%
“…EB1 recognizes GTP-bound tubulin in the GTP-cap region at the plus-end of microtubules. 42 The more proximal binding of EB3 is consistent with EB3 recognizing GDP-bound tubulin. The differential localization of these two +TIP proteins on the same microtubule has implications for the consequences of drebrin binding to EB3.…”
Section: Discussionmentioning
confidence: 75%